a= 1 b=4 c= 3
-4 ± √ (4)²- 4 (1) (3)
2 (1)
-4 ± √ 16-12
2
-4 ±√4
2
-4 ± 2
2
x1= -4+2 x2= -4-2
2 2
x1= -2 x2= -6
2 2
x1= -1 x2= -3
x² - 5x - 24= 0
a= 1 b= -5 c= -24
-(-5)± √ (-5)²- 4 (1) (-24)
2 (1)
5± √ 25 + 96
2 (1)
5± √ 121
2
5± 11
2
x1= 5+11 x2= 5-11
2 2
x1= 16 x2= -6
2 2
x1= 8 x2= -3
a= 2 b= -1 c= -6
-(-1)± √ (-1)²- 4 (2) (-6)
2 (2)
-1± √ 1- 48
4
-1± √ 49
4
-1± 7
4
x1= 1+7 x2= 1-7
4 4
x1= 8 x2 = -6
4 4
x1= 2 x2= -3
2
x² - 6x + 8= 0
a= 1 b= -6 c= 8
-(-6)± √ (-6)²- 4 (1) (8)
2 (1)
6± √ 36- 32
2 (1)
6± √ 4
2
6± 2
2
x1= 6+2 x2= 6-2
2 2
x1= 8 x2= 4
2 2
x1= 4 x2= 2
x² - 9x + 20= 0
a= 1 b= -9 c= 20
-(-9)± √ (-9)²- 4 (1) (20)
2 (1)
9± √ 81- 80
2 (1)
9± √ 1
2 (1)
9± 1
2
x1= 9+1 x2= 9-1
2 2
x1= 10 x2= 8
2 2
x1=5 x2= 4
No hay comentarios:
Publicar un comentario